2021
DOI: 10.18632/aging.203553
|View full text |Cite
|
Sign up to set email alerts
|

miR-19b-3p relieves intervertebral disc degeneration through modulating PTEN/PI3K/Akt/mTOR signaling pathway

Abstract: Emerging studies have revealed that non-coding RNAs contribute to regulating intervertebral disc degeneration (IVDD). Here, we intended to probe into the function of miR-19b-3p in IVDD evolvement. The miR-19b-3p level in the intervertebral disc (IVD) tissues of IVDD patients and IL-1β/TNF-α/hydrogen peroxide-treated human nucleus pulposus cells (HNPCs) was determined by quantitative real-time polymerase chain reaction (qRT-PCR). Also, qRT-PCR was conducted to exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…Recent studies have suggested that mTOR signalling is critical for maintaining IVD homeostasis. 24,25 Based on existing literature, we focused on the mTOR signalling pathway and its multiple biological functions in IVD cells to comprehensively clarify the role of the mTOR signalling pathway in IDD.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have suggested that mTOR signalling is critical for maintaining IVD homeostasis. 24,25 Based on existing literature, we focused on the mTOR signalling pathway and its multiple biological functions in IVD cells to comprehensively clarify the role of the mTOR signalling pathway in IDD.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that activation of AKT signaling attenuated NPC apoptosis induced by high-magnitude compression or hyperosmotic conditions [ 49 ]. In addition, AKT could protect NPCs against apoptosis induced by some cytokines, such as IL-1β and TNF-α [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that TNF-α leads to disorganization of cell metabolism in IVD, including reduction of Col-2 as well as aggrecan, and elevation of MMPs and ADAMTSs, which contribute to the destruction of the ECM and pathogenesis of IVDD ( Liu Y. et al, 2021 ; Zhao and Li, 2021 ). TNF-α promotes the expression levels of catabolic markers, including MMP-13 and ADAMTS-5, which are harmful to ECM components during IVDD.…”
Section: Discussionmentioning
confidence: 99%